Effects of foreign direct investment in African agriculture. Issue 2 (5th May 2015) - Gunasekera, Don; Cai, Yiyong; Newth, David
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to review the key issues surrounding foreign direct investment (FDI) in agriculture, and examine the potential impacts of FDI in African agriculture. Design/methodology/approach – The dynamic Global Trade Analysis Project model (GDyn) is used to analyse the potential impacts of improvements in land productivity and FDI in Africa. Findings – The results illustrate that combined efforts to improve land productivity and growth in FDI could potentially increase Africa's share in global agricultural output and exports, particularly with respect to oil seeds, sugar, and cotton. Originality/value – The authors employ a global economy-wide modelling framework to simulate the effects of growth in FDI in African agriculture.